Sex differences in disease: sex chromosome and immunity - Zuxi Feng; Minjing Liao; Liansheng Zhang (Journal of Translational Medicine)
Abstract Sex is a fundamental biological variable that influences immune system function, with sex chromosomes (X and Y) playing a central role in these differences. Despite substantial evidence of disparities in immune responses between males and females, biomedical research has historically overlooked sex as a critical factor. This oversight has contributed to the observed disparities in susceptibility to autoimmune diseases, infectious diseases, and malignancies between the sexes. In this review, we address the phenomena and mechanisms through which aberrant expression of sex chromosome-linked genes contributes to sex-based differences in immune responses. We specifically focus on the implications of X chromosome inactivation (XCI) escape and loss of Y chromosome (LOY). Our review aims to elucidate the molecular mechanisms driving these sex-based differences, with particular emphasis on the interactions between sex chromosome genes and immune cells in both males and females. Additionally, we discuss the potential impact of these differences on disease susceptibility and identify prospective therapeutic targets. As personalized and precision medicine advances, it is crucial to integrate sex differences into immunological research and clinical trials. We advocate for an increased focus on sex-based considerations in fundamental, translational, and clinical research to promote personalized, sex-specific healthcare.